THE CRITICAL LEVEL OF WATER INFILTRATION MAPPING IN GAJAHMUNGKUR AND CANDISARI SUB-DISTRICTS, SEMARANG CITY - Budianta, Wawan; Adhi Putra, Bagas; Dewi Titisari, Anastasia (KURVATEK, 2023)
The high rate of urbanization in the city of Semarang has an impact on sustainable development which continues to be intensified by the government, accompanied by changes in the function of water infiltration areas to become infrastructure areas. This change in land use causes the water infiltration area to decrease. Therefore, research was carried out on the critical level of the water infiltration area in Gajahmungkur and Candisari Districts, Semarang City, to determine the condition of the critical level and the size of each critical level. The research was carried out by collecting primary data through mapping soil types and lithology in the field and secondary data, including land use data and slope, which will be verified later in the area. The data above will then be analyzed using the Analytical Hierarchy Process (AHP) method by weighing each parameter and subparameter. The parameters are soil type, land use, slope, and lithology. These weightings are then overlaid to produce a zoning map of the critical level of the water infiltration area in Gajahmungkur and Candisari Districts, Semarang City. The study area’s critical level of water infiltration areas can be divided into good, naturally normal, started to be critical, slightly critical, critical, and very critical.